Metode Menentukan Mitra Bisnis Pada â€œKomunitas Tanpa Ribaâ€ Di Malang - khusnudin us din (Jurnal Ilmiah Ekonomi Islam, 2023)
Business activities will be more accessible if done with partners. Determining the right business partner is the main factor in achieving the business's success. The interrelation of the parties in running the business to gain profits will be easier with suitable partners. Various methods are used to determine the right business partner. The determining factors of a business partner's feasibility that satisfy the needs of a non-profit community is an interesting research topic. Qualitative research was conducted using a phenomenological approach with "La Riba Community" as the subject. In-depth interview data were analyzed using interpretive phenomenological analysis. Results of the study found that â€œLa Riba Communityâ€ used the safar method for three days to determine whether someone would fit to become a partner or vice versa. Theoretically supports the concept of Islamic business ethics by involving the Allah in finding the right partner